Evaluation of Different High Κ Materials for In situ Growth of Carbon Nanotubes. (25th August 2016) - Keyn, Martin; Krauss, Tillmann Adrian; Kramer, Andreas; Schwalke, Udo
Abstract : In this work we investigate the in situ growth of carbon nanotubes (CNTs) on different dielectric stacks for use in discrete field-effect transistor devices. While CNT growth is demonstrated on all stacks, only devices fabricated on atomic layer deposited aluminum oxide show sufficiently reliable gate dielectrics. Electrical burn pulses are applied to the devices to selectively remove undesired metallic CNTs in order to obtain proper transistor behavior with an on/off current ratio of five orders of magnitude.